Age independent survival benefit for patients with hepatocellular carcinoma (HCC) without metastases at diagnosis: a population-based study. Issue 1 (16th March 2019) - De Toni, Enrico N; Schlesinger-Raab, Anne; Fuchs, Martin; Schepp, Wolfgang; Ehmer, Ursula; Geisler, Fabian; Ricke, Jens; Paprottka, Philipp; Friess, Helmut; Werner, Jens; Gerbes, Alexander L; Mayerle, Julia; et al.
Abstract : Objective: Hepatocellular carcinoma (HCC) is a major cause of death worldwide and its incidence is expected to increase globally. Aim of this study was to assess whether the implementation of screening policies and the improvement of treatment options translated into a real-world survival benefit in HCC patients. Design: 4078 patients diagnosed with HCC between 1998 and 2016 from the Munich Cancer Registry were analysed. Tumour characteristics and outcome were analysed by time period and according to age and presence of metastases at diagnosis. Overall survival (OS) was analysed using Kaplan-Meier method and relative survival (RS) was computed for cancer-specific survival. Cox proportional hazard models were conducted to control for prognostic variables. Results: While incidence of HCC remained substantially stable, tumours were diagnosed at increasingly earlier stages, although the median age at diagnosis increased. The 3 years RS in HCC improved from 19.8% in 1998–2002, 22.4% in 2003–2007, 30.6% in 2008–2012 up to 31.0% in 2013–2016. Median OS increased from 6 months in 1998–2002 to 12 months in 2008–2016. However, analysis according to the metastatic status showed that survival improved only in patients without metastases at diagnosis whereas the prognosis of patients with metastatic disease remained unchanged. Conclusion: These real-world data show that, in contrast to the current assumptions, the incidence of HCC did not increase in a representative German region. Earlier diagnosis, likely related to the implementation of screening programmes, translated into an increasing employment of effective therapeutic options and a clear survival benefit in patients without metastases at diagnosis, irrespective of age.